Composition and Characteristics of Rock Vibration Generated in Blasting Excavation of Deep Tunnels - Yang, Jianhua; Sun, Jinshan; Jia, Yongsheng; Yao, Yingkang; Zhang, Weipeng; Tao, Tiejun (Frontiers in Earth Science, 2022)
During blasting excavation in deep rock masses, the in situ stress initially exerted on blast-created free surfaces is rapidly released along with rock cracking by blasting. The rapid stress release can initiate seismic waves transmitting through the medium. In addition to explosion loading, the rapid stress release occurring on blast-created free surfaces is another excitation source of the rock vibration generated in blasting excavation of deep rock masses. In this paper, a theoretical model of seismic wave radiation from a circular blasting excavation in a deep rock mass is first developed to study the frequency differences between explosion seismic waves and stress release-induced seismic waves. Based on this, variational mode decomposition (VMD) is then introduced to separate explosion seismic waves and stress release-induced seismic waves from coupled vibration signals in the frequency domain. By utilizing the VMD separation, the composition and the amplitude and frequency characteristics of the rock vibration monitored in an actual deep tunnel blasting are investigated. The theoretical analysis and field investigation show that the vibration frequency of stress release-induced seismic waves is significantly lower than that of explosion seismic waves. Due to the existence of stress release-induced seismic waves with lower frequency, the coupled vibration amplitude is increased and vibration frequency is reduced. The monitored rock vibration in the near field is dominated by explosion seismic waves. However, in the far field, stress release-induced seismic waves become the major component due to their lower frequency and slower attenuation with distance. Extra care should be taken for the stress release-induced seismic waves in the far field. The stress release-induced seismic waves can be effectively reduced through shortening blast-created free surface sizes and increasing blasthole lengths moderately.